EVALUATING THE USABILITY AND EFFECTIVENESS OF ELECTRONIC HEALTH RECORDS IN PUBLIC HOSPITALS: A MIXED METHODS STUDY - Abdulrahman Saif Alsahli, Turki Marzoq Alshammari, Mohammed Esmail Yahya Adawi Hashdi, Fahad Marzoq Alshammari, Saleh Buniah E Alshammari, Abdulsalam Hmooud Ammash Alshammari (Chelonian Research Foundation, 2022)
Electronic health records (EHRs) are being adopted globally, but robust evaluations in public hospital contexts are lacking. This concurrent embedded mixed methods study evaluated nurses’ perspectives on EHR usability and impacts 6 months after implementation across 10 public hospitals. Surveys using the System Usability Scale and satisfaction questionnaires were completed by 150 nurses. Additionally, 15 nurses participated in semi-structured interviews eliciting experiences. EHR usage data provided utilization metrics. Survey results showed mean usability score of 82/100 indicating high usability but revealed areas needing workflow refinement. Interviews emphasized insufficient training, hardware gaps causing delays, and impatience with initial productivity declines before efficiency benefits. However, metrics showed rapid uptake within 6 months. An integrated analysis approach provided comprehensive insights into barriers and facilitators. Tailored training for functionality and workflows, leadership support during transitional productivity dips, and continuous quality improvement are advised for effective EHR adoption. The study provides a model for user-centered, context-sensitive evaluation to guide system optimizations and change management for maximal EHR effectiveness in enhancing care coordination and outcomes.